Study on an Undershot Cross-Flow Water Turbine with Straight Blades - Yasuyuki Nishi; Terumi Inagaki; Yanrong Li; Kentaro Hatano (International Journal of Rotating Machinery)
Small-scale hydroelectric power generation has recently attracted considerable attention. The authors previously proposed an undershot cross-flow water turbine with a very low head suitable for application to open channels. The water turbine was of a cross-flow type and could be used in open channels with the undershot method, remarkably simplifying its design by eliminating guide vanes and the casing. The water turbine was fitted with curved blades (such as the runners of a typical cross-flow water turbine) installed in tube channels. However, there was ambiguity as to how the blades’ shape influenced the turbine’s performance and flow field. To resolve this issue, the present study applies straight blades to an undershot cross-flow water turbine and examines the performance and flow field via experiments and numerical analyses. Results reveal that the output power and the turbine efficiency of the Straight Blades runner were greater than those of the Curved Blades runner regardless of the rotational speed. Compared with the Curved Blades runner, the output power and the turbine efficiency of the Straight Blades runner were improved by about 31.7% and about 67.1%, respectively.